E-071 Percutaneous alcohol embolization of symptomatic vertebral hemangioma using column technique: a case report. (22nd July 2019) - Male, S; Mehta, T; Khan, A; Grande, A; Tummala, R; Jagadeesan, B
Abstract : Background: Hemangiomas are the most common vertebral body tumors typically discovered as incidental findings on spinal imaging. In 1% of patients, hemangiomas can be symptomatic causing persistent back pain that necessitate treatment. Percutaneous alcohol embolization (PAE) is an effective but challenging way of treating these lesions. We hereby report a case of vertebral hemangioma treated with PAE with unique technique. Methods: 59-year-old man with chronic back pain refractory to medications, physical therapy and chiropractic maneuvers presented to our clinic. His MRI spine revealed multiple vertebral hemangiomas, most prominent at T8 and T10. On examination, the point of maximum tenderness was at T10. Limited spinal angiogram revealed tumor blush at the sites of vertebral hemangiomas. Under sterile conditions, two 10-gauge needles were advanced in the T10 vertebral body via transpedicular approach. The contrast injection revealed tumor blush and venous outflow into the azygous system. For PAE, we formed columns of contrast-absolute ethanol-contrast to avoid alcohol dilution and for adequate visualization during embolization. (figure 1) A bubble trapped between these columns, initially inadvertently and later intentional, also helped to keep the columns separate. The mixing of contrast to absolute ethanol is an alternative to this technique. However, it could decrease the efficacy of absolute ethanol in obliteration of hemangioma. Patient tolerated the procedure very well and endorsed clinical improvement on day 1. Conclusion: During PAE for vertebral hemangiomas, formation of columns of contrast and absolute ethanol during embolization is an effective technique. It helps to preserve higher alcohol concentration and in turn, efficacy of embolization while maintaining adequate visualization. Disclosures: S. Male: None. T. Mehta: None. A. Khan: None. A. Grande: None. R. Tummala: None. B. Jagadeesan: None.